Rhyme and Its Rhythmic and Semantic Significance - Kalmin, Hamz (El Omda in Linguistics and Discourse Analysis, 2023)
This research addresses the Arabic rhyme as an essential structural element in the construction of Arabic poetry, due to the various features and functions it encompasses, whether at the rhythmic level or the semantic level. For this reason, rhyme has been examined through a descriptive and analytical approach, with reference to its definition, its constituent letters, and its possible defects, before discussing in detail its importance in terms of meaning and rhythm. The study concludes that Arabic rhyme contains multiple phonetic and semantic dimensions that contribute significantly to shaping the Arabic poem both structurally and semantically.